Influence of Growth Temperature on Morphological and Structural Properties of Sputtered- Zinc Oxide Nanorods - Bao Quan Tran; Hai Dang Ngo; Thi Kim Hang Pham (Journal of Technical Education Science, 2024)
Zinc oxide is highly sought after for several applications in biology, optoelectronics, electronics, and sensing. Zinc oxide nanorods exhibit a high exciton binding energy and a wide direct band gap, making them an attractive material for ultraviolet optoelectronic devices in the compound semiconductor field. This investigation focuses mainly on the influence of growing temperature on the crystal structure and surface morphology of ZnO nanorods, specifically for their application as UV photodetectors. Si (100) substrates were utilized for the growth of ZnO nanorods using radio frequency magnetron sputtering. The ZnO nanorods are grown at temperatures of 350 °C, 375 °C, and 400 °C, respectively. The crystal structure and surface morphology were examined using X-ray diffraction and scanning electron microscopy. The samples exhibited a same crystal orientation of the (002) diffraction peak at all growth temperatures. The growth temperatures show a direct influence on the density and length of nanorods, as evidenced by the scanning electron microscopy photographs. The results revealed the significant influence of substrate temperature on the regulation of nanorod length and crystal formation.